2019
DOI: 10.1242/bio.047233
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of ribosomes in Drosophila axons using Ribo-BiFC

Abstract: The distribution of assembled, and potentially translating, ribosomes within cells can be visualised in Drosophila by using Bimolecular Fluorescence Complementation (BiFC) to monitor the interaction between tagged pairs of 40S and 60S ribosomal proteins (RPs) that are close neighbours across inter-subunit junctions in the assembled 80S ribosome. Here we describe transgenes expressing two novel RP pairs tagged with Venus-based BiFC fragments that considerably increase the sensitivity of this technique we termed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Given the complexity of dendritic arbors, this is achieved through local protein translation at distal dendrites and axons [ 59 ]. The presence of ribosomes in dendrites and axons has long been established [ 59 , 60 , 61 ]. Studies have also demonstrated that activity-dependent local protein translation leads to the remodeling of the actin cytoskeleton which in turn modulates dendritic spine morphology [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of dendritic arbors, this is achieved through local protein translation at distal dendrites and axons [ 59 ]. The presence of ribosomes in dendrites and axons has long been established [ 59 , 60 , 61 ]. Studies have also demonstrated that activity-dependent local protein translation leads to the remodeling of the actin cytoskeleton which in turn modulates dendritic spine morphology [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of dendritic arbors, this is achieved through local protein translation at distal dendrites and axons (Holt, Martin and Schuman, 2019). The presence of ribosomes in dendrites and axons has long been established (Holt, Martin and Schuman, 2019; Singh et al ., 2019; Lottes and Cox, 2020). Studies have also demonstrated that activity dependent local protein translation leads to remodeling of the actin cytoskeleton which in turn modulates dendritic spine morphology (Nakahata and Yasuda, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of cOMe in Drosophila, both the CBC and EJC are reduced at synapses indicating that cOMe provides a mark for certain mRNAs to be transported in an untranslated state to synapses for local translation. [14,71] Intriguingly, CMTr2 targets in Drosophila are enriched in transcripts also targeted by FMR1, the homologue of human FMRP which has been shown to regulate protein synthesis. [14,72] In fact, the translational repressive role of FMRP in arresting ribosomes on mRNAs is consistent with a role of cOMe in directing untranslated mRNAs to synapses.…”
Section: Functions Of the Cap And Methylated Cap-adjacent Nucleotides...mentioning
confidence: 99%
“…In the absence of cOMe in Drosophila , both the CBC and EJC are reduced at synapses indicating that cOMe provides a mark for certain mRNAs to be transported in an untranslated state to synapses for local translation. [ 14,71 ]…”
Section: Functions Of the Cap And Methylated Cap‐adjacent Nucleotides...mentioning
confidence: 99%